2021
DOI: 10.3390/cells10040762
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Fates of Pyruvate in Normal and Neoplastic Cells

Abstract: Pyruvate occupies a central metabolic node by virtue of its position at the crossroads of glycolysis and the tricarboxylic acid (TCA) cycle and its production and fate being governed by numerous cell-intrinsic and extrinsic factors. The former includes the cell’s type, redox state, ATP content, metabolic requirements and the activities of other metabolic pathways. The latter include the extracellular oxygen concentration, pH and nutrient levels, which are in turn governed by the vascular supply. Within this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 274 publications
(478 reference statements)
0
57
0
Order By: Relevance
“…However, in response to oncogenic transformation or rapid normal cell proliferation, more extensive transcriptional regulation of glucose uptake and its oxidation in response to elevated Myc is achievable (Nesbit et al 1999; Meyer and Penn 2008; Dolezal et al 2017; Kalkat et al 2017; Wang et al 2018; Mathsyaraja et al 2019). This could have the additional benefit of sustaining cell division when micro-environmental glucose and oxygen were limiting and nutrient-dependent functions of MondoA and ChREBP were attenuated (Prochownik and Wang 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in response to oncogenic transformation or rapid normal cell proliferation, more extensive transcriptional regulation of glucose uptake and its oxidation in response to elevated Myc is achievable (Nesbit et al 1999; Meyer and Penn 2008; Dolezal et al 2017; Kalkat et al 2017; Wang et al 2018; Mathsyaraja et al 2019). This could have the additional benefit of sustaining cell division when micro-environmental glucose and oxygen were limiting and nutrient-dependent functions of MondoA and ChREBP were attenuated (Prochownik and Wang 2021).…”
Section: Discussionmentioning
confidence: 99%
“…6) whereas, in response to Myc-driven transformation or normal proliferation, more extensive transcriptional regulation of glucose uptake and its oxidation is achievable [4, 14, 23, 25, 49, 78]. This could have the additional benefit of maximizing glycolytic efficiency and sustaining cell division when micro-environmental glucose and oxygen supplies were limiting and nutrient-dependent functions of MondoA and ChREBP were attenuated [79].…”
Section: Discussionmentioning
confidence: 99%
“…Through the oxidation by active un-phosphorylated PDH, pyruvate would be converted to acetyl-CoA in the mitochondria. After entering the TCA cycle, acetyl-CoA enables mitochondria either to generate ATP to meet the energy demand or to derive fatty acids for the biosynthesis of phospholipids or amino acids for the biosynthesis of proteins, which are cornerstones for tumor growth, progression, and invasion [11,54]. Interestingly, as compared to the control, our results revealed that PDH became more phosphorylated after a mild TFAM knockdown but less phosphorylated after an obvious TFAM knockdown (Figure 2A).…”
Section: Discussionmentioning
confidence: 80%
“…In glycolysis, glucose can produce pyruvate by glycolytic enzymes with hexokinase (HK) as the first step [10]. Converted by pyruvate dehydrogenase (PDH), pyruvate, which is considered a central metabolic node [11], joins the TCA cycle in the form of acetyl-CoA to release high energy intermediates, the reduced flavin adenine dinucleotide (FADH 2 ), and reduced nicotinamide adenine dinucleotide (NADH). Under the premise of sufficient oxygen supply, FADH 2 and NADH would generate ATP through electron transport and OXPHOS [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It may however follow this route under normal oxygen conditions in a process called “aerobic glycolysis” or Warburg effect ( Figure 1 ), named after the Nobel laurate Otto Warburg who described this phenomenon as a fingerprint of tumor physiology ( Warburg, 1956 ). Although demonized because of its elevated levels in cancer, aerobic glycolysis also takes place in normal cells and tissues under conditions where a high proliferation rate is required, as it is also used to provide the cell with metabolic intermediates ( Hume and Weidemann, 1979 ; Lunt and Vander Heiden, 2011 ; Liberti and Locasale, 2016 ; Prochownik and Wang, 2021 ).…”
Section: The Toolkitmentioning
confidence: 99%